Cultivating Empathy Through Virtual Reality: Advancing Conversations About Racism, Inequity, and Climate in Medicine. (December 2020) - Roswell, Robert O.; Cogburn, Courtney D.; Tocco, Jack; Martinez, Johanna; Bangeranye, Catherine; Bailenson, Jeremy N.; Wright, Michael; Mieres, Jennifer H.; Smith, Lawrence
Abstract : Problem: Racism and bias are fundamental causes of health inequities, and they negatively affect the climate of academic medical institutions across the United States. Approach: In 2019, the Zucker School of Medicine and Northwell Health piloted a virtual reality (VR) racism experience as a component of professional development for medical school and health system leaders, faculty, and staff. Participants experienced a 60-minute, interactive, large-group session on microaggressions and, as individuals, a 20-minute VR module. These were followed by group reflection and debriefing. The sessions, developed in collaboration with a VR academic team, represented a response to institutional climate assessment surveys, which indicated the need for expanded professional training on cross-cultural communication and enhancing inclusion. Outcomes: In October 2019, 112 faculty and staff participated in the workshop. On a postworkshop survey, completed by 76 participants (67.9%), most respondents (90.8%) reported feeling engaged in the VR experience. Additionally, the majority agreed that VR was an effective tool for enhancing empathy (94.7%), that the session enhanced their own empathy for racial minorities (85.5%), and that their approach to communication would change (67.1%). In open-ended responses, participants frequently conveyed enthusiasm, powerful emotional and physiologic responses, and enhanced empathy. They also suggested more time for follow-up discussions. Next Steps: Next steps include assessing the scalability of the VR module; determining effective complementary engagements; and measuring the module's longitudinal effects on racial empathy, discrimination, and institutional climate. As VR becomes more common in medical education, developing VR modules to address other forms of discrimination (e.g., sexism, homophobia) could also benefit the institutional climates of medical schools and health systems as academic medicine continues to build toward health equity. Abstract : Supplemental Digital Content is available in the text.